Pemodelan Dinamika Baterai LiFePo4 Berbasis Model Rangkaian Equivalent Thevenin Orde-1 - Muhamad Dzaky Ashidqi; Silviana Windaasari; Mardiyan Dama; Adi Affandi Ratib (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
Accurate battery modeling is crucial for the development of battery-based energy storage systems, especially for real-time control and energy management applications. This study proposes a dynamic parameter modeling approach for LiFePO₄ batteries using a first-order Thevenin equivalent circuit model. Parameter estimation is performed to obtain the internal battery parameters based on the Thevenin model, and the parameter dynamics are derived using the Euler numerical method to represent battery behavior during charging and discharging processes. Model validation is conducted by comparing the predicted terminal voltage with actual measurements using root mean square error (RMSE) and mean absolute error (MAE) as evaluation metrics. The results show that the model accurately captures the battery dynamics, with an RMSE of 0.233 and an MAE of 0.047. Therefore, the proposed model is suitable for real-world applications that require accurate and dynamic estimation of internal battery parameters.